Prognostic and Clinicopathological Role of PD-L1 in Endometrial Cancer: A Meta-Analysis - Lu, Ling; Li, Yonghong; Luo, Rong; Xu, Junhui; Feng, Jie; Wang, Mingqiang (Frontiers in Oncology, 2020)
Background: A series of studies have explored the prognostic value of programmed death-ligand 1 (PD-L1) in patients with endometrial cancer (EC); however, the results are controversial. Therefore, this meta-analysis was performed to estimate the associations between PD-L1 expression and the prognosis and clinicopathological features of EC. Methods: A comprehensive literature search of PubMed, Web of Science, and Embase was conducted up until September 06, 2019. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS) and progression-free survival (PFS) were computed using the random-effects model (REM) or fixed-effects model (FEM). Odds ratios (ORs) and 95% CIs were calculated to evaluate the relationship between PD-L1 and clinicopathological factors. Results: A total of 9 studies with 1,615 patients were included in the meta-analysis. The combined data showed that high expression of PD-L1 was not significantly correlated with OS (HR=1.20, 95% CI=0.41–3.52, p=0.737) or PFS (HR=1.12, 95% CI=0.50–2.54, p=0.778) in EC. In addition, PD-L1 expression was significantly associated with poor differentiation (OR=2.82, 95% CI=1.96–4.06, p<0.001) and advanced stage (OR=1.71, 95%CI=1.12–2.60, p=0.013). Conclusion: This meta-analysis suggests that PD-L1 expression is not associated with poor prognosis in patients with EC. However, PD-L1 expression is positively correlated with poor differentiation and advanced tumor stage in EC.